1999
DOI: 10.2527/1999.7792469x
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid digestibilities in different samples of wheat shorts for growing pigs.

Abstract: An experiment was carried out to investigate the variability in apparent ileal amino acid (AA) digestibilities in simulated samples of wheat shorts consisting of different proportions of wheat bran (WB), wheat shorts (WS), and wheat flour (WF), hereafter referred to as wheat fractions. The proportions of WS, WB, and WF and the NDF content (DM basis) of the wheat fractions were as follows: A, 70% WS, 30% WB, and 42.3% NDF; B, 85% WS, 15% WB, and 41.8% NDF; C, 100% WS and 41.3% NDF; D, 85% WS, 15% WF, and 35.2% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 0 publications
4
23
1
Order By: Relevance
“…However, the digestibilities were usually lowest in the wheat fractions containing wheat bran. These results are in general agreement with those reported by Graham et al (1986a) who found that the dietary inclusion of wheat The neutral detergent fibre content (% DM) and apparent ileal digestibility (%) of crude protein and limiting amino acids in the wheat fractions (Huang et al, 1999) …”
Section: Cerealssupporting
confidence: 83%
See 1 more Smart Citation
“…However, the digestibilities were usually lowest in the wheat fractions containing wheat bran. These results are in general agreement with those reported by Graham et al (1986a) who found that the dietary inclusion of wheat The neutral detergent fibre content (% DM) and apparent ileal digestibility (%) of crude protein and limiting amino acids in the wheat fractions (Huang et al, 1999) …”
Section: Cerealssupporting
confidence: 83%
“…The effect of variation in fibre content in wheat fractions on protein and amino acid digestibility in pigs was studied by Jondreville et al (1995) and recently by Huang et al (1999). In the earlier studies on wheat fractions containing from about 7 to 48% NDF, they found negative correlations between ADF content, or proportion of total N bound to NDF, and true ileal digestibilities of crude protein and all amino acids.…”
Section: Cerealsmentioning
confidence: 91%
“…Mucin is very rich in Thr, which accounts for up to 30% of its AA composition (Neutra and Forstner, 1987). The fact that mucin is the main constituent of endogenous protein excretion could explain the low Thr digestibility generally reported (Marichal-Landin et al, 1995;Huang et al, 1999).…”
Section: Prediction Of Standardized Ileal Digestibility Of Essential mentioning
confidence: 99%
“…Wheat by-products, such as WB and WM are produced when wheat is processed into flour for human consumption (Laurinen et al, 1998;Huang et al, 1999). Moreover, the use of wheat for bio-ethanol production results in the production of various by-products such as wDDGS, wheat wet distillers solubles and condensed distillers solubles (Widyaratne and Zijlstra, 2007a;Pahm et al, 2008b;Pedersen and Lindberg, 2010).…”
Section: Introductionmentioning
confidence: 99%